Internal jugular distensibility index as a predictor of fluid responsiveness in adult patients undergoing elective surgery – A prospective accuracy study - Dita Aditianingsih; Aldy Heriwardito; Laksmi Senja Agusta; El Nissi Leonard; Chrisella Annabelle (Indian Journal of Anaesthesia)
Background and Aims: Assessing the intravascular volume is necessary in patients undergoing surgery, but predicting how the body will respond to fluid can be challenging. Evaluation of the internal jugular vein distensibility index (IJV-DI) is an alternative method to determine intravascular volume status. This study aims to determine the suitability of measuring stroke volume by using IJV-DI measurement compared with transthoracic echocardiography in assessing the fluid responsiveness in elective surgery patients. Methods: This prospective study involved 79 subjects undergoing elective surgery under general anaesthesia. Following anaesthesia induction, IJV-DI and stroke volume measurements were performed before and after fluid administration. Subjects experiencing an increase in stroke volume of more than 10% were categorised as responders. The primary outcome was the suitability of IJV-DI in determining fluid responsiveness compared to transthoracic echocardiography in elective surgery patients. The data were then analysed to assess its diagnostic value using the receiver operator characteristic (ROC) curve, the appropriate cut-off point using the Youden index, and the correlation using Spearman’s correlation test. Results: A total of 45 subjects were responders. Our analysis revealed an area under the curve (AUC) value of 0.871 (95% CI: 0.790, 0.951). The optimal cut-off value was found at an internal jugular vein distensibility index of >12.62% with a sensitivity of 84.4% and a specificity of 79.4%. A moderate positive correlation existed between the index and stroke volume increase (r = 0.535, P < 0.001). Conclusion: IJV-DI assessment is compatible with transthoracic echocardiography stroke volume measurement for evaluating elective surgery patients’ fluid response.